The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1365-2591.2004.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors affecting post‐obturation pain in patients undergoing root canal treatment

Abstract: The prevalence of post-obturation pain was high (40.2%). The important prognostic determinants of post-obturation pain were female, molar tooth, size of periapical lesion smaller than 3 mm, history of post-preparation pain or generalized swelling and single-visit treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
182
12
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(232 citation statements)
references
References 23 publications
21
182
12
5
Order By: Relevance
“…9 Previous research, have shown that factors such as age, sex, dental pulp status, allergies and pain before treatment have a primary role in causing these pains. 10 Although the non-steroidal anti-inflammatory drugs for pain associated with endodontic therapy have been used, these medications have relatively large side effects in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 Previous research, have shown that factors such as age, sex, dental pulp status, allergies and pain before treatment have a primary role in causing these pains. 10 Although the non-steroidal anti-inflammatory drugs for pain associated with endodontic therapy have been used, these medications have relatively large side effects in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Post obturation pain is the pain of any degree after endodontic treatment 5 . Development of pain after completion of RCT may undermine patient's confidence in the clinician and acceptance of the procedure 6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, patients in the KF group, where the glide path was performed with hand files, showed a significantly higher analgesic tablets consumption per individual. Mechanical, chemical, or microbial injuries to the periradicular tissues are frequent causes of pain complication (19). Indeed, most cases of post-operative pain are caused by acute periradicular inflammation, such as acute periodontitis or acute periradicular abscess secondary to intracanal procedure (20).…”
mentioning
confidence: 99%